An Efficient Mathematical Approach for an Indoor Robot Localization System - AL-Forati, Israa Sabri A.; Rashid, Abdulmuttalib; Al-Assfor, Fatemah (Iraqi Journal for Electrical and Electronic Engineering, 2019)
In a counterfeit clever control procedure, another productive methodology for an indoor robot localization framework is arranged. In this paper, a new mathematic calculation for the robot confinement framework utilizing light sensors is proposed. This procedure takes care of the issue of localization (position recognizing) when utilizing a grid of LEDs distributed uniformly in the environment, and a multi- portable robot outfitted with a multi-LDRs sensor and just two of them activate the visibility robot. The proposed method is utilized to assess the robot’s situation by drawing two virtual circles for each two LDR sensors; one of them is valid and the other is disregarded according to several suggested equations. The midpoint of this circle is assumed to be the robot focus. The new framework is simulated on a domain with (n*n) LEDs exhibit. The simulation impact of this framework shows great execution in the localization procedure.